Stability analysis in rice landraces grown under dry Direct seeded condition (Bangladesh Journal of Botany, 2023)
In the present study the genotype x environment interaction and stability performances of 15 rice landraces  in Rabi season during 2017-18 to 2021-22 at Agricultural Research Station, Tamil Nadu Agricultural University,  Tamil Nadu, India were evaluated. Eberhart - Russel model was used for stability analysis in rice. In this model, genotype mean across environments, regression of genotype on environmental index and  function of the squared deviation from the regression were determined. Mean sum of squares against environment source of variation as well as linear component of environment were significant for all the studied characters suggesting a presence of variation among the environments tested. The linear component of genotype x environment interaction was also found  significant for all the traits studied which  indicated  presence of significant differences between  the genotypes. The landraces Kallurundaikar and Kattanur responded favourably to better environments but gave poor yield in an unfavourable environment. Hence, they are suitable for favourable environments. Sivappuchithiraikar and Mysore malli recorded the highest grain yield with bi value closer to unity and non-significant deviation from regression. They were reported as stable genotypes and recommended for cultivation in southern districts of Tamil Nadu.Bangladesh J. Bot. 52(4): 941-948, 2023 (December)